The interactive relationship between binocular vision and executive ability: a study based on neural mechanisms and clinical impact - ZHANG Li; LIU Wenyan; CHENG Linxing; LIN Zhi; SHEN Tao (Yanke Xuebao)
Binocular vision, the ability of both eyes to work simultaneously, coordinate, and integrate visual information, can produce a unified, three-dimensional, and depth-perceptive visual experience. In recent years, it has garnered increasing attention in cognitive psychology and neuroscience research, particularly in exploring its complex relationship with executive functions. Executive functions, as a crucial cognitive capability, encompass various aspects, including attention, working memory, decision-making, and problem-solving, all of which collectively influence an individual's performance and efficiency in daily life and work. Current research indicates that binocular vision plays a key role not only in processing visual information but also has a significant impact on an individual's executive functions. Groups with binocular vision abnormalities (such as strabismus and amblyopia patients) generally exhibit characteristics like delayed response inhibition and reduced working memory capacity in executive function tests. However, existing literature on the relationship between binocular vision and executive functions, especially systematic analyses based on neural mechanisms and their clinical implications, remains relatively insufficient. Therefore, this article reviews existing research to delve into the role of binocular vision in executive functions, analyzes the underlying neural mechanisms in detail, and discusses the potential clinical implications of these findings. Additionally, the article proposes future research directions to comprehensively understand the complex interplay between binocular vision and executive functions,aiming to provide new perspectives and ideas for research in related fields and promote further development in this area.